The Leadership Competencies in Family Business: A Case Study of A Family Business Company in Surabaya - Thesia Agatha Patria; Alvin Kristanto (iBuss Management, 2018)
There has been an emergence of family businesses in Indonesia in the recent years. Its significance can be equalized as the backbone of most of the country’s economy. The researchers are interested and fortunately found the opportunity to explore deeply the impact of leadership in family businesses for the case of PT. ABC.In this research, the case study found that there are similarities and differences in how leaders across management level in PT. ABC practice the leadership competencies. Taking on qualitative approach by using interviews, this research found that the similarities and differences are coming from how leaders practice strong ethics and safety; empowering others to self-organize; efficient learning; nurtures growth as well as sense of connection and belonging. Some of the elements described in each competency are practiced by the leaders, while some are not or are practiced in different ways. However, to the extent of the aforementioned competencies, the leaders believe in the importance of practicing system across all level of management. While the owner can still bypass the system in a way, the need for a leader to create a system in controlling the business is irreplaceable. Keyword: Leadership, Family Business, Strong Ethics and Safety, Empowering Others, Efficient Learning, Nurturing, Sense of Connection and Belongings, System